Efficacy of maximun anchoring using transpalanance and double ATP in cases requiring first superior premolar extractions : a comparative analysis = Eficacia del anclaje máximo usando transpalanance y doble ATP en casos de extracciones de primeros premolares superiores: análisis comparativo - Ubilla Mazzini, William
Introduction: Space maintainers play an important role in orthodontic treatments involving premolar extractions, especially in cases with bad occlusion and marked crowding. The orthodontist must know several options of anchoring and choose the best method that would fulfill the treatment objectives for that patient. Objective: To compare the effects of maximum anchors like the double transpalatal arch (double ATP) and the transpalatal arch and Nance button combination (transpalanance) as space maintainers during cuspids retraction in patients undergoing upper bicuspid extractions. Methods: A universe of 100 patients, aged 14-25 years, was selected from among the patients presenting to the Orthodontics Specialty Clinic of the posgraduate School Dr. José Apolo Pineda, Pilot School of Dentistry, University of Guayaquil during the years of 2017 and 2018. Totally, 26 patients were recruited, of whom 13 were placed on transpalanance and the other 13 on double ATP, prior to the extraction of their first upper bicuspid. Post-extraction spaces were measured and compared with post-retraction spaces of upper cuspids. Results: With an average of 4-5 mm, transpalanance maintained the greatest amount of space at the end of canine retraction. It is expected that the results obtained in this study will be useful to orthodontists, providing them with information regarding the most effective space maintainers for treatments with extractions. Conclusion: The maximum anchor that showed the greatest efficacy was transpalanance since it maintained a greater amount of space during its time of use.